Characteristics differences between pure porous and non-porous of Bl1.6Pbo.4Sr2Ca2Cu3-XO10 superconductors / Muhamad Shamsul Bahriel Abd Rahman - Abd Rahman, Muhamad Shamsul Bahriel (Faculty Of Applied Sciences, 2017)
The non-porous (Bi, Pb)-2223 superconductor has of has high density, but low critical current density, Jc value which is able to allow more current flows through the material. So, the porous (Bi, Pb)-2223 superconductor was introduced to improve the superconductivity properties of the superconductor. The improvement can be made through the electrical resistance characteristics such as the critical current density, Jc of the material. Jc is the measure of the maximum current that can flow in the wire without a resistance in superconducting materials. The non-porous (Bi, Pb)-2223 superconductor has a high density, but it loses superconducting properties because of low critical current density. Therefore, it is important to find out the difference of nonporous (Bi, Pb)-2223 superconductor with the porous one. Due to limitation of time, only Tc is able to find out. The Tc of the samples was investigated using four-point probe resistance test. The experimental results of non-porous (Bi, Pb)-2223 superconductors show a metallic-like behavior curve pattern, while the porous one shows neither superconductor, nor semi-conductor, nor even metallic behavior probably because of the large amount of crystalline sucrose added into the (Bi, Pb)2223.